A Case-Control Study Examining the Relationship between Gastroesophageal Reflux Disease and Dental Caries - P Suganya; P Nimmy; S Savitha; R. P. Srutheesri; M Anita; Charumathi Dhanushkodi; Savitha Lakshmi Raghavan (Journal of Pharmacy and Bioallied Sciences)
Aim: This case-control study aims to assess the association between gastroesophageal reflux disease (GERD) and dental caries among individuals aged 18–35 years in Chennai city, India. Materials and Method: The study included 350 participants, divided equally into GERD and non-GERD groups, identified using a six-item GERD questionnaire. Dental caries was assessed using the DMFT index, and the body mass index (BMI) was calculated for each participant. The collected data were analyzed using analysis of variance. Results: Significant association was found between GERD and higher DMFT scores, with GERD patients exhibiting more decayed, missing, and total teeth compared to non-GERD patients. Conclusion: These findings underscore the need for integrated dental and medical care for GERD patients, emphasizing weight management to mitigate GERD symptoms. The study provides valuable insights into the interplay between GERD, dental caries, and BMI in a young adult population.